Black Minstrelsy on Canadian Stages: Nostalgia for Plantation Slavery in the Nineteenth and Twentieth Centuries - Thompson, Cheryl (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2021)
Blackface minstrelsy, which began in the American northeast in the 1820s and 1830s, featured White, mostly male performers, who crossed racial boundaries by mimicking African Americans with the supposedly “authentic” music, humour, and dance ostensibly common on southern plantations. By the 1860s, newly emancipated African Americans also performed on stages in blackface. By the end of the nineteenth century, however, Black actors performed out of blackface, but they were still required to perpetuate stereotypes plucked from the plantation. These troupes were led by both Black and White managers who promoted their performances as “authentic” and “nostalgic.” These elements of the black minstrel show — most prominently its supposedly “real” depictions of the American South and plantation slavery — resonated with Canadian audiences. It therefore provides another lens — outside of immigration policies and de facto Jim Crow — through which to explain the presence of anti-Black racism and xenophobia in late-nineteenth and early-twentieth-century Canada. By examining the content of black minstrelsy, the role its managers play in its productions, and promotion in newspapers, this article raises questions about the extent to which Canadians have been historically complicit in the denigration of Black people.